Mode Interaction in Wide Plate with Angle Section Longitudinal Stiffeners Under Compression - Kołakowski, Z. (Engineering Transactions, 1989)
Interaction of nearly simultaneous buckling modes in the presence of imperfections is studied. The investigation is concerned with infinitely wide plate with thin-walled angle longitudinal stiffeners under uniform compression.The asymptotic expansion established by BYSKOV and HUTCHINSON [1] is also used here. The present paper is devoted to the improved study of equilibrium path in the initial postbuckling behaviour of imperfect structures with regard to the effect of interaction of the global mode and two local buckling modes.